THE DIGITAL DIVIDEND: EXPLORING THE POTENTIAL OF DIGITAL TRANSFORMATION FOR SUSTAINABLE ECONOMIC DEVELOPMENT IN UZBEKISTAN - Ayodeji, Gabriel (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
Rapid advancements in digital technology have transformed economies worldwide, prompting governments to prioritize digital transformation as a key driver of economic growth and sustainability. This study examines the impact of digital transformation on economic growth and sustainability in Uzbekistan. Through a comprehensive analysis of perceptions, initiatives, and economic indicators, the research explores the relationship between digitalization and key outcomes. Quantitative methods, including correlation analysis, regression analysis, inferential statistics, hypothesis testing, and thematic analysis, were employed to analyze survey data and draw insights. The findings reveal significant positive correlations between perceptions of digital transformation, its implementation, and economic indicators such as job creation, public service efficiency, and environmental sustainability. The study also identifies challenges related to resource constraints, regulatory environments, and the digital divide, which hinder the full realization of digitalization's potential. Based on these findings, the study offers theoretical implications, practical recommendations, and suggestions for future research to inform policy and practice in fostering digital transformation for inclusive and sustainable development in Uzbekistan and similar contexts.